Advancing the best interests of the child in South African family-related legal disputes - Clarke, Sharna-Lee (Department of Public Law, 2025)
This thesis examines the extent to which South Africa complies with international standards in protecting the best interests of the child in family-related legal disputes. The thesis applies a doctrinal methodology, drawing on primary sources such as international treaties, South African legislation, and case law, as well as secondary sources, including academic literature and general comments from treaty bodies. The thesis argues for an approach to protecting the best interests principle that encompasses substantive elements that should guide the courts when determining what is in the child's best interests; and procedural safeguards to ensure that the child's substantive rights are protected during the decision-making process. This approach emphasises the recognition of children as autonomous rights holders with evolving and developing capacities and needs and the significance of their participation in decision-making processes. The thesis finds that, in general, South Africa's legal framework aligns strongly with substantive elements and procedural safeguards of the best interests principle as developed by international child rights law. The analysis of the practice of the best interests principle in international child abduction decision-making reveals that South African courts generally succeed in incorporating substantive elements into the decision-making process. However, significant procedural challenges, including delays in appointing legal representation, resource constraints, and inefficiencies in expediting decisions, undermine the consistent protection of children's rights. These procedural shortcomings often hinder the practical realisation of the best interests principle, particularly in time-sensitive contexts like international child abduction cases. To address these challenges, the thesis recommends targeted procedural reforms. This includes mandating the timely appointment of independent legal representatives for children in all abduction cases, supported by clear guidelines and adequate resources. It further advocates for ongoing training for legal professionals representing children and the development of specialised multidisciplinary support services to ensure holistic and child-focused decision making. These refinements would serve to harmonise procedural efficiency with substantive protections, thereby enhancing the implementation of the best interests principle in practice